Characteristics of three strains of avian adenoviruses isolated in Queensland. II. Biochemical, biophysical, and electron microscope studies - Mustaffa Babjee, Ahmad; Spradbrow, P. B. (American Association of Avian Pathologists, 1975)
Three strains of adenovirus were relatively stable to the effects of chloroform, extreme pH, trypsin, heat, lyophilization, and ultrasonication. The structure of the viruses and their mode of replication in cell cultures confirmed these viruses to be members of the avian adenoviruses.